2007
DOI: 10.1103/physrevlett.99.227002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Leggett’s Collective Mode in a MultibandMgB2Superconductor

Abstract: We report observation of Leggett's collective mode in a multiband MgB2 superconductor with Tc=39 K arising from the fluctuations in the relative phase between two superconducting condensates. The novel mode is observed by Raman spectroscopy at 9.4 meV in the fully symmetric scattering channel. The observed mode frequency is consistent with theoretical considerations based on first-principles computations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
133
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 29 publications
8
133
0
Order By: Relevance
“…Its double-gap structure originates from an electronic structure around the Fermi energy that comprises σ and π bands [33][34][35] . Observation of the Leggett mode in MgB 2 has been reported with tunneling spectroscopy 36 , Raman spectroscopy 37,38 and angle-resolved photoemission spectroscopy 39 , while no report has so far been made for the Higgs mode. A more recent family of superconductors, the iron pnictides with high T c s, also have multi-orbital and multi-gap structures, where the electron correlation is suggested 40,41 to bring about s ± and s ++ pairings depending on the chemical composition and/or doping level 42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Its double-gap structure originates from an electronic structure around the Fermi energy that comprises σ and π bands [33][34][35] . Observation of the Leggett mode in MgB 2 has been reported with tunneling spectroscopy 36 , Raman spectroscopy 37,38 and angle-resolved photoemission spectroscopy 39 , while no report has so far been made for the Higgs mode. A more recent family of superconductors, the iron pnictides with high T c s, also have multi-orbital and multi-gap structures, where the electron correlation is suggested 40,41 to bring about s ± and s ++ pairings depending on the chemical composition and/or doping level 42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…We stress that this is an estimate as the dip location is slightly affected by functional form of the self energy. The vertex corrections for Raman spectroscopy 25,30 and ARPES are almost certainly different and can potentially explain the the difference between the Leggett mode energy measured by the two techniques. Previous electron spectroscopy studies reported the value of the Leggett mode energy of 3.9-4.0 meV, consistent with our results.…”
mentioning
confidence: 99%
“…Previous electron spectroscopy studies reported the value of the Leggett mode energy of 3.9-4.0 meV, consistent with our results. While the bare mode was calculated to have a frequency of 5.1-6.2meV 25,30 , if the experimentally measured ∆ π = 1.5meV is used, the calculated frequencies decrease to 3.8-4.5meV. More theoretical efforts will be required to fully understand the origin of the difference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the Leggett modes in multi-band superconductor have already attracted intensive interests [24][25][26][27][28][29]. It is only until very recently years that some evidences of its existence have been observed experimentally in multi-band superconductors MgB 2 , by tunneling spectroscopy techniques [30], Raman spectroscopy [31], and angle-resolved photoemission spectroscopy [32]. In the case of cold atom system, the Leggett modes have so far not been observed experimentally.…”
mentioning
confidence: 99%